PENGARUH LATIHAN PNF (PROPRIOCEPTIVE NEOUROMUSCULAR FACILITATION) DAN LATIHAN PLIOMETRIK TERHADAP KECEPATAN TENDANGAN DWIHURIGI DALAM OLAHRAGA TAEKWONDO - Annisha Fathni Fathimah, - (2022)
The background of this research is from the results of the analysis of the researchers that taekwondo athletes still have difficulty in doing double kicks both in practice and in competitions. The purpose of this study was to determine "the effect of PNF training and plyometric training on double kick speed in taekwondo". The research method used is an experimental research method using One Group Pre-test Post-Test Design . The data collection technique was carried out by giving an initial test / pre-test to a group called the experimental group. Then given treatment with PNF training methods and plyometric exercises. The data processing technique uses three methods, namely normality test, homogeneity test, and Paired Sample T-Test. The population used in this study were taekwondo athletes of Pelatcab Kabupaten Bandung. The sample that the author uses is Total Sampling of 10 people . The study was conducted for 6 weeks with 12 meetings. The results showed that PNF training and plyometric training had a significant effect on the speed of double kicks in taekwondo. So it can be concluded that the PNF training method and plyometric training have a significant effect on the speed of double kicks in taekwondo.